VALUATION OF MOUNT MERAPI NATIONAL PARK: A TRAVEL COST ANALYSIS - Dewanta, Awan Setya (Economic Journal of Emerging Markets, 2011)
This study estimates recreational value of Taman Nasional Gunung Merapi (TNGM – Mount Merapi National Park) in Kaliurang, Yogyakarta with a travel cost method. Since the visitors are not the frequent ones, the paper estimates the visitor’s utility using a categorical regression technique. Applying in-depth interview on visitors from August 1st until August 15th 2009, the results suggest that the utility function for recreation at volcano national park is better estimated using the negative binomial distribution model. It also finds that the economic value of recreation at volcano national park is Rp 222,000, and that the total consumer surplus for recreation national park is Rp 31.2 billion. Keywords: Travel cost valuation, binomial regression model, recreation national park valuation JEL classification numbers: D12, L83